(3YeGdI GdGWaGd Hjf GdhGbY hGdJTQjY(B. (3OQGSI ejOGfjI HGdYjfI (B((3fehPL eOjfI UjOG(B)s - (3YdGA GdOjf, YHjQs ((3HjQhJs (3GdLGeYI GddHfGfjI (B- (3eYgO GdYdhe GdGLJeGYjIs, 2006)
(3JgOa GdOQGSI Edi JSdjW GdVhA Ydi hGbY YeGdI GdCWaGd aj Gdegf GdMQajI hGdUfGYjI hGdJLGQjI hPdc Vef eOjfI UjOG, hYQV GdfbGW GdeKjQI ddLOd Mhd GdEJaGbjGJ hGdJTQjYGJ GdJj JJHfGgG GdOhdI GddHfGfjI ef LgI hYOe GdSYj LOjkG Edi eJGHYI hJfajP TQhW gPg GdGJaGbjGJ(B. (3EYJeOJ GdOQGSI Ydi GdYOjO ef GdefGgL, efgG efgL OQGSI GdMGdI, GdhUaj, GdHfGFj GdhXjaj, Gdcdj GdESJfHGWj, GdESJbQGFj, GdEMUGFj, GdeSM GdELJeGYj(B. (3ESJNOeJ GdedGMXI, GdebGHdI, hGdGSJeGQI(B. (3Je JMOjO KdGK hMOGJ dOQGSJgG, GdChdi gj (B93 (3UGMH efTCI Ch UGMH Yed MjK jYed GdCWaGd, GdKGfjI (B137 (3WadkG jYedhf aj GdeOjfJjf GdUfGYjJjf aj UjOG, GdKGdKI gj CSQ GdCWaGd GdYGedI (B(137 (3CSQI(B)(3, HGdEVGaI Edi (B11 (3WadkG dG jedchf CSQkG ge ef GdLfSjI GdShQjI Ch GdeUQjI Ch GdadSWjfjI(B. (3HjfJ GdfJGFL GfJTGQ XGgQI YeGdI GdCWaGd aj eOjfI UjOG, hJhVM GdOQGSI Cf GdefTBJ GdMQajI GdJj JSJNOe CWaGdkG, ZGdHG eG jJeJY CUMGHgG HeSJhi JYdjej efNaV, hTQhW GdYed ajgG dG JNJda Hjf cHGQ Ch CWaGd HGdfSHI ddYGedjf, ceG dG jdYH YeQ GdYGed OhQkG aj YedjI ESJNOGe GdBdGJ hGdeYOGJ GdJj JTcd NWQkG Ydi GdUMI GdLSOjI, hGdfSHI GdCcHQ ef gPg GdefTBJ JaJbQ Edi GdYOjO ef GdTQhW GdUMjI(B. (3ceG JdYH GdNUGFU GdEbJUGOjI hGdELJeGYjI hGdJYdjejI ddCSQI OhQkG gGekG aj JbQjQ eUjQ GdCHfGA GdOQGSj hGdegfj, ajCJj GdLGfH GdeJYdb HGdTCf GdJQHhj aj WdjYI GdCSHGH GdeDOjI Edi YeGdI GdCWaGd, hjdjgG GdLGfH GdEbJUGOj(B. (3ChVMJ GdOQGSI Cf ZGdHjI GdefTBJ GdMQajI dG JWHb bhGfjf GdYed GddHfGfjI GdJj JMXQ ESJNOGe GdCWaGd bHd Sf GdKGdKI YTQI, hHPdc fSJOd Edi ZjGH GdQbGHI GdaYdjI ddeDSSGJ GdMchejI hGdCgdjI, hGdJbUjQ GdaGVM aj JfajP HfhO GdEJaGbjGJ GdJj UqObJ YdjgG GdOhdI GddHfGfjI(B.s
(3GdfhY (B: (3QSGdIs
Keywords: Child Labor; Travail des enfants; (3UjOGs; (3YeGdI GdGWaGd hCWaGd GdThGQYs